Optimising Biology Learning Outcomes of Grade X Students at MAN 1 Pamekasan through the Implementation of the Problem-Based Learning (PBL) Model - Ida Firnanda; Mabrurotul Rosidah; Moch Haikal; Linta Wafdan Hidayah; Destha Ramadanty Prasutri (DIDAKTIKA : Jurnal Penelitian Tindakan Kelas, 2025)
Low cognitive learning outcomes among students in Madrasah Aliyah continue to be a challenge for meaningful learning in biology. This study aimed to enhance the cognitive learning outcomes of Grade X students at MAN 1 Pamekasan by applying the Problem-Based Learning (PBL) model. This classroom action research employed the Kemmis and McTaggart model and was conducted in two cycles in one Grade X class at MAN 1 Pamekasan; each cycle consisted of planning, action, observation, and reflection stages. The research instruments were essay and short-answer tests covering cognitive domains C1 to C4. The results showed an increase in the students’ mean score from 72.8 in Cycle I to 81.7 in Cycle II. The percentage of learning mastery increased from 82.6% to 87.0%. A paired-sample t-test indicated a statistically significant improvement (t(22) = 2.64, p = 0.008) with a medium effect size (d = 0.549). These findings indicate that the PBL model is effective for improving students’ cognitive learning outcomes in Biology learning in madrasah aliyah.